Sinergi Inklusi dan Literasi Keuangan dalam Memacu Pertumbuhan Ekonomi Indonesia: Analisis Empiris Menggunakan Pendekatan Autoregressive Distributed Lag (ARDL) - Yasrizal Yasrizal; Sailal Arimi; Aglis Andhita Hatmawan (Indo Publishing, 2025)
This study analyzes the dynamics of the relationship between financial inclusion, financial literacy, and Indonesia's economic growth during the 2013–2025 period. With the Indonesia Emas 2045 agenda as context, the study highlights structural issues in the form of the gap between expanding access to financial services (inclusion) and public understanding (literacy). Using a quantitative approach through the Autoregressive Distributed Lag (ARDL) model, the study tests for the existence of long-term cointegration while estimating short-term adjustment mechanisms through error correction. Stationarity tests indicate a combination of degrees of integration I(0) and I(1), making the selection of ARDL (1, 0, 0) relevant. The main results confirm the existence of a cointegration relationship: financial inclusion has a positive and significant impact on GDP in the long run with a coefficient of 0.15, while financial literacy contributes positively, primarily through strengthening more stable consumption behavior. The Error Correction Term (ECT) coefficient of -0.68 indicates a relatively rapid recovery process, with approximately 68% of the deviation from the long-run equilibrium corrected within one year. The research's contribution lies in utilizing the latest post-pandemic data and evaluating the implications of the National Strategy for Financial Inclusion (SNKI). Policy recommendations emphasize a shift from solely focusing on infrastructure expansion to strengthening the capabilities of financial service users, in order to mitigate the risks of predatory inclusion and ensure higher-quality and sustainable growth.